Comparison of neoadjuvant chemoimmunotherapy and chemotherapy alone for resectable stage III non-small cell lung cancer: a real-world cohort study - Zhou, Sihao; Liu, Yi; Liu, Kejun; Zhang, Junkai; Liang, Hanlin; Wu, Yingmeng; Ye, Hongyu; Liang, Yi; Zhang, Jingjing; Huang, Weizhao (Frontiers in Immunology, 2023)
We compared the real-world efficacy and safety of neoadjuvant chemoimmunotherapy to chemotherapy alone in patients with stage III non-small-cell lung cancer (NSCLC).Participants and methods: A total of 59 consecutive patients were finally selected and divided into two groups: the neoadjuvant chemotherapy group (n = 33) and the neoadjuvant chemoimmunotherapy group (n = 26). The primary endpoint was disease-free survival (DFS). The 删除[Accdon]: This is a provisional file, not the final typeset article secondary endpoints were pathological response, clinical response, and adverse events. All patients were followed up to collect perioperative pathology and clinical data.The objective response rate (ORR), pathological complete response (pCR), and major pathological response (MPR) were significantly higher in the neoadjuvant chemoimmunotherapy group than in the neoadjuvant chemotherapy group (73.1% vs. 45.5%, 34.6% vs. 3.0%, and 65.3% vs. 15.1%, respectively; P < 0.05). There was no statistically significant difference in disease-free survival between the neoadjuvant chemoimmunotherapy and neoadjuvant chemotherapy groups (P = 0.129). Patients in the neoadjuvant chemoimmunotherapy group had a higher rate of tumor regression than those in neoadjuvant chemotherapy group (37.0% [40 patients] vs. 29.0% [30 patients], P = 0.018). However, no discernible correlation between MPR achievement and the degree of tumor shrinkage was observed in either group (P > 0.05). The cumulative MPR rates were 42.3, 50, and 65.3% for 2, 3, and ≥ 4 cycles, respectively, in the neoadjuvant chemoimmunotherapy group and 9.1, 12.1, and 15.1% for ≤ 2, 3, and ≥ 4 cycles, respectively, in the neoadjuvant chemotherapy group.Moreover, No statistical difference was observed between the two groups regarding postoperative complications, resection range, operation time, surgical method, and extent of resection (P > 0.05).Although the incidence of grades III-IV adverse events was higher in the neoadjuvant chemotherapy group than in the neoadjuvant chemoimmunotherapy group (33.3% vs. 4.6%, P = 0.042), there was no significant difference in the incidence of adverse events between the two groups (64.6% vs. 83.6%, P = 0.072).In stage III NSCLC, neoadjuvant chemoimmunotherapy achieved higher pathological and clinical remission rates than chemotherapy alone, with compromising safety, making it an attractive choice for neoadjuvant therapy.